Sujeitos emblemáticos à luz do sintagma identidade-metamorfose-emancipação: produções acadêmicas do NEPIM - Griebeler, Deborah (2015)
The present dissertation aims to study the term "Emblematic subjects" as a theoric contribution to the Theory of the Identity in construction, sustained in the syntagma identity-metamorphosis-emancipation proposed by Ciampa (1987). According to a survey carried out during the process of this work, the term "Emblematic subjects" have been used and built since 1996 in discussions at NEPIM (Center of Study and Research of Identity-Metamorphosis) of Pontifical Catholic University of São Paulo (PUC-SP). To carry out this study, we began, so, with academic productions of NEPIM that have had completed the term "Emblematic subjects" and, as a methodology, we used the history of life contained in the eight academic works that served as a base for short account that are presented here as contextualization and illustration of what is discussed now. This work designed in the syntagma identity-metamorphosis-emancipation proposed by Ciampa (1987) and the arising from productions of NEPIM, and has as a theoric reference Jürgen Habermas and Ciampa, especially the post-conventional subject of Habermas (1983) and the "come to be" and "be to itself" of Ciampa (1987). As we treat it like a theoric work, this dissertation ends with the final considerations broaching synthetically, what has been discussed throughout the work such as exposing inherent gaps to the academic production as possible spaces of appropriation of the Academy